INDICATION OF SAFE POISON MATERiA^-S FROM INDIGENOUS PLANTS FOR CLEARING .UNWANTED FISHES FROM NURSERY PONDS - Shirgur, Girish A (Indian Journal of Fisheries, 2011)
Etadication of unwanted fishes is an essential prerequisite for a scientific management of perennial nursery ponds and stocking ponds. Routine nettings is’not a fool’pro<S’fm6th<3d. Htence for total or near-totd eradication, a wide range of piscicides were being eiiipldyed. Until recently synthetic insecticides (fc.g. Tafdrin^io, with 20% Endrin was copimonly! being used) which are very effective killers were used for this purpose